An Adaptive Machine Learning Framework Integrating AutoML and MLOps for Two‐Stage Classification in Hard Disk Drive Manufacturing - Natthakritta Rungtalay; Somyot Kaitwanidvilai (IET Collaborative Intelligent Manufacturing, 2025)
ABSTRACT This study aims to predict hard disk drives (HDDs) that pass initial testing but fail during reliability testing, using historical data from 8968 records with 218 features, such as head position and flying height of the read/write head. Since reliability testing is time‐intensive, early failure prediction can significantly accelerate problem detection and resolution. The research focuses on detecting fly height modulation, a key symptom of HDD failure, and introduces an adaptive machine learning (ML) framework integrating AutoML for optimised model selection and hyperparameter tuning with MLOps for deployment, monitoring and continuous updates. Building on a previously proposed dual‐stage classification framework that combines novelty detection and supervised learning, the proposed framework addresses the inefficiencies of manual hyperparameter tuning inherent in the earlier methods. The proposed framework achieves 92% accuracy in novelty detection and 100% in supervised learning, outperforming prior approaches. This integration of AutoML and MLOps offers a scalable, robust solution for early failure prediction, enabling real‐time adaptability with minimal human intervention. Future work will focus on enhancing computational efficiency and responsiveness to data shifts and drifts, advancing data‐driven decision‐making in reliability testing.
Keywords: Machine Learning and Data Classification; Data Stream Mining Techniques; Neural Networks and Applications